Differences according to Sex in Sociosexuality and Infidelity after Traumatic Brain Injury - Jhon Alexander Moreno; Michelle McKerral (Behavioural Neurology)
Objective. To explore differences according to sex in sociosexuality and infidelity in individuals with TBI and in healthy controls. Participants. Forty-two individuals with mild, moderate, and severe TBI having completed a postacute TBI rehabilitation program, at least six months after injury, and 47 healthy controls. Main Measures. Sociosexual Orientation Inventory-Revised (SOI-R) and Attitudes toward Infidelity Scale. Results. Overall, men score significantly higher than women in sociosexuality. However, there was a nonsignificant trend towards a reduction of sociosexuality levels in men with TBI. Infidelity levels were comparable in healthy controls and individuals with TBI. In individuals with TBI, less acceptance of infidelity was significantly associated with an unrestricted sociosexual orientation, but not in healthy controls. Conclusions. As documented in previous cross-cultural studies, men have higher levels of sociosexuality than women. However, men with TBI showed a tendency towards the reduction of sociosexuality. The possibility of a latent explanatory variable is suggested (e.g., post-TBI neuroendocrinological changes). TBI does not seem to have an impact on infidelity, but individuals with TBI who express less acceptance of infidelity also report a more promiscuous mating strategy regarding their behavior, attitudes, and desire. Theoretical implications are discussed in terms of evolutionary theories of human sexuality and neuropsychology.